Effects of Lactiplantibacillus plantarum on Metabolites and Flavors in Synthetic Microbiota During Baijiu Fermentation - Chunyue Yan; Xurui Chen; Quan Liu; Tengyu Xu; Qian Zhang; Xueli Jin; Bei Liao; Xiong Chen; Xin Li (Foods)
The distinctive flavor and aroma of Chinese baijiu are closely linked to the microorganisms involved in the fermentation process. Lactiplantibacillus plantarum, a dominant species in the fermentation of Chinese baijiu, has become a prominent research focus. In this study, we selected well-characterized pure cultures of microorganisms to construct diverse chassis microflora. The primary objective was to investigate the effects of L. plantarum on the fermentation process of Chinese baijiu and its association with metabolites produced by different chassis microflora. Our results demonstrated that the concentrations of ethyl lactate and other volatile aromatic compounds increased in all fermentation protocols where L. plantarum was added. The addition of L. plantarum also significantly increased the concentration of total organic acids, particularly lactic acid, which rose by 17 to 123 times. Furthermore, L. plantarum helped maintain the stability of ethanol concentration during the middle and late stages of fermentation. Notably, among the three different chassis microbial fermentation protocols involving L. plantarum, the protocol with the highest microbial diversity exhibited a greater capacity to produce lactic acid (1.56 ± 0.19 mg/g), ethanol (5.74 ± 0.47 mg/g), and reducing sugars (6.39 ± 0.31 mg/g). These findings provide valuable insights into the potential of L. plantarum for modulating the flavor of Chinese baijiu.